Residential green environments are associated with human milk oligosaccharide diversity and composition - Lahdenperä Mirkka; Galante Laura; Gonzales-Inca Carlos; Vahtera Jussi; Pentti Jaana; Rautava Samuli; Käyhkö Niina; Yonemitsu Chloe; Gupta Julia; Bode Lars; Lagström Hanna (Nature Portfolio, 2025)
Increased exposure to greener environments has been suggested to lead to health benefits in children, but the associated mechanisms in early life, particularly via biological mediators such as altered maternal milk composition, remain largely unexplored. We investigated the associations between properties of the mother's residential green environment, measured as (1) greenness (Normalized Difference Vegetation index, NDVI), (2) Vegetation Cover Diversity (VCDI) and (3) Naturalness Index (NI), and human milk oligosaccharides (HMOs), known for their immune- and microbiota-related health effects on the infant (N=795 mothers). We show that HMO diversity increases and concentrations of several individual HMOs and HMO groups change with increased VCDI and NI in residential green environments. This suggests that variation in residential green environments may influence the infant via maternal milk through modified HMO composition. The results emphasize the mediating role of breastfeeding between the residential green environments and health in early life.